Phase 1 study of intravenous administration of the chimeric adenovirus enadenotucirev in patients undergoing primary tumor resection. - Garcia-Carbonero, R; Salazar, R; Duran, I; Osman-Garcia, I; Paz-Ares, L; Bozada, J; Boni, V; Blanc, C; Seymour, L; Beadle, J; Alvis, S; Champion, B; et al. (BioMed Central, 2017)
Background Enadenotucirev (formerly ColoAd1) is a tumor-selective chimeric adenovirus with demonstrated preclinical activity. This phase 1 Mechanism of Action study assessed intravenous (IV) delivery of enadenotucirev in patients with resectable colorectal cancer (CRC), non-small-cell lung cancer (NSCLC), urothelial cell cancer (UCC), and renal cell cancer (RCC) with a comparator intratumoral (IT) dosed CRC patient cohort. Methods Seventeen patients scheduled for primary tumor resection were enrolled. IT injection of enadenotucirev (CRC only) was administered as a single dose (≤ 3 × 1011 viral particles [vp]) on day 1, followed by resection during days 8–15. IV infusion of enadenotucirev was administered by three separate doses (1 × 1012 vp) on days 1, 3, and 5, followed by resection during days 8–15 (CRC) or days 10–25 (NSCLC, UCC, and RCC). Enadenotucirev activity was measured using immunohistochemical staining of nuclear viral hexon and quantitative polymerase chain reaction for viral genomic DNA. Results Delivery of enadenotucirev was observed in most tumor samples following IV infusion, with little or no demonstrable activity in normal tissue. This virus delivery (by both IV and IT dosing) was accompanied by high local CD8+ cell infiltration in 80% of tested tumor samples, suggesting a potential enadenotucirev-driven immune response. Both methods of enadenotucirev delivery were well tolerated, with no treatment-associated serious adverse events. Conclusions This study provides key delivery and feasibility data to support the use of IV infusion of enadenotucirev, or therapeutic transgene-bearing derivatives of it, in clinical trials across a range of epithelial tumors, including the ongoing combination study of enadenotucirev with the checkpoint inhibitor nivolumab. It also provides insights into the potential immune-stimulating properties of enadenotucirev.